Landscape-driven environmental variability largely determines abiotic characteristics and phytoplankton patterns in peat bog pools (Tierra del Fuego, Argentina) - Mataloni, Maria Gabriela (2015)
Ombrotrophic peat bogs from Tierra del Fuego are characteristically raised, dome-shaped, fed by precipitation, and nutrient-poor. Their landscape pattern consists of a Sphagnum magellanicum matrix encompassing pools with different morphometric and trophic features. Within the framework of a 2-year limnological survey in five pools from Rancho Hambre peat bog, we analyzed phytoplankton communities under the hypothesis that taxonomic composition would show a spatial pattern driven by ultimately landscape-controlled environmental features such as pH and trophic status, while temperature and weather-dependent features would account for seasonal changes in abundance and structure. Among the 305 taxa recorded, most were Conjugatophyceae and Bacillariophyceae, and were strongly associated to circumneutral pH and minerotrophic conditions, though limited superficial connectivity among pools accounted for dissimilar taxonomic compositions. Despite such differences, phytoplankton of pools with similar morphometry and trophic status showed similar dominant and richest taxonomic groups undergoing paralell changes over time. Seasonal temperature fluctuations were modulated by pool size and modified not only abiotic properties but also phytoplankton abundance, with different taxa showing strong summer peaks in different pools. An interpretative model is proposed which will be tested as a tool for predicting community strategy and temporal variation patterns as responses to different environmental templates.